1998
DOI: 10.1063/1.122281
|View full text |Cite
|
Sign up to set email alerts
|

Red-light-emitting injection laser based on InP/GaInP self-assembled quantum dots

Abstract: Red-light-emitting quantum dot injection lasers have been prepared by solid-source molecular beam epitaxy. The separate confinement heterostructure contains densely stacked layers of self-assembled InP quantum dots embedded in Ga0.51In0.49P waveguide and Si/Be-doped Al0.53In0.47P cladding layers. Edge-emitting laser diodes are processed, which show quantum dot lasing at 90 K. Thereby, the threshold current density is 172 A/cm2. The energy of the laser line is at 1.757 eV, which is very close to the peak energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…1 In addition it has been shown that quantum dot lasers can have broad gain spectra, which are of interest for applications such as continuously tunable sources 2 and extremely short pulse generation. 3 InP dots in GaInP have also aroused interest, [4][5][6] motivated by the potential benefits of dots in general and, specifically, by the possibility of extending the upper-wavelength limit of conventional, compressively strained, GaInP quantum wells from 690 nm to the region of 750 nm for growth on GaAs substrates. In this letter we report the results of an investigation of the photoluminescence (PL) and optical gain properties of InP/ GaInP quantum dot structures for different growth rates and for growth on vicinal (100) and ͑211͒B GaAs substrates.…”
mentioning
confidence: 99%
“…1 In addition it has been shown that quantum dot lasers can have broad gain spectra, which are of interest for applications such as continuously tunable sources 2 and extremely short pulse generation. 3 InP dots in GaInP have also aroused interest, [4][5][6] motivated by the potential benefits of dots in general and, specifically, by the possibility of extending the upper-wavelength limit of conventional, compressively strained, GaInP quantum wells from 690 nm to the region of 750 nm for growth on GaAs substrates. In this letter we report the results of an investigation of the photoluminescence (PL) and optical gain properties of InP/ GaInP quantum dot structures for different growth rates and for growth on vicinal (100) and ͑211͒B GaAs substrates.…”
mentioning
confidence: 99%
“…The epitaxial growth of self-assembled QD systems allows the realization of small QDs in high densities with excellent crystal quality [3]. Laser operation has already been demonstrated by several groups using different material systems such as In(Ga)As/(Al,Ga)As [4,5], InP/(Al)GaInP [6], CdSe/ZnSe [7] and, optically excited, InGaN/GaN [8]. Also, by varying QD composition and electronic properties within each material system, it should be possible to obtain laser emission over a wide spectral range.…”
Section: Introductionmentioning
confidence: 97%
“…For laser applications, a high density of QDs is desirable [7], while for quantum-information applications, a low density of QDs is preferred to get single photon emission by preventing the coupling between QDs [8]. Of particular practical interest are nanostructures with InP QDs that can be used to fabricate the laser structures emitting in the red spectral range [9]. InP/InGaP QDs are also promising candidates for applications demanding isolated single quantum systems with emission in the spectral window of highest Sibased detector efficiency.…”
Section: Introductionmentioning
confidence: 98%